Tropical forest recreation: Visitors’ experience and satisfaction in Kinabalu Park, Sabah - Hamimah Talib (2011)
The use of tropical forest parks as recreation resource is receiving increasing response from the public. Although its contribution as a recreational resource is apparent, more in-depth information on how it relates to and benefits the users are still unclear. The purpose of this study is to understand the recreation experience and satisfaction of visitors in a tropical forest park setting with the use of mixed method approach (quantitative and qualitative techniques) incorporating two models/theories as the research framework. Six hundred and nine questionnaire surveys and forty-two interviews were conducted with purposively sampled visitors in two specific sites and activities in Kinabalu Park: 1) Mt. Kinabalu (MK) climbing in Kinabalu Park headquarters area, and 2) Canopy Walkway (CW) visit in Poring Hot- Spring Station. The Recreation Experience Preference (REP) scale was used to elicit visitors’ experience types gained through participation, and in-depth interview analysis based on Motivation-Hygiene Theory was conducted to understand their experience and satisfaction. This study found that the experience for MK ranges from “Achievement-Stimulation” (highest mean score) to “Security-Comfort zone” (lowest mean score), and experience for CW ranges from “Enjoy Nature-Learning” (highest mean score) to “Socialization” (lowest mean score). In-depth interview analysis findings lend credence to the Motivation-Hygiene Theory, where visitors’ satisfying experience involved attributes originated from personal psychological needs to grow, intrinsic and intangible in nature (motivation factors). Meanwhile, visitors’ dissatisfaction involved attributes originated from physical conditions, extrinsic, and tangible in nature (hygiene factors). This study contributes to the understanding of visitors’ recreational experience and satisfaction in tropical forest parks context, especially how the experiences satisfy personal psychological needs, which highlights the values and importance of this resource. This study however limits itself to focus on the interrelationship between recreation experience and satisfaction, thus did not look in detail into the phenomenological elements of recreation experience. Recommendations for park management and avenues for future studies were identified and discussed.